Bella i Sebastian - Aubry, Cecile (Warszawa : Nasz Ksiegarnia, 1987)
The story of a young Gypsy orphan, Sebastian and his dog Bella, taking place in the wilds of the French Alps. Ages 8-12.
Tom I, Schronisko pod wielkim baou.--Tom II, Tajny dokument.